Dampak Konversi Lahan Pertanian terhadap Kesejahteraan Petani dan Perkembangan Wilayah: Studi Kasus di Daerah Bandung Utara - Agus Ruswandi; Ernan Rustiadi; Kooswardhono Mudikdjo (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishAgricultural land conversion occurred as a logical consequense of development activities in a particular region. As a matter of fact, land conversion has mostly generated negative impact in the context of food security and farmer’s socio economic condition. The studies of macro aspects on land conversion have been conducted frequently but studies on micro aspects were still rarely carried out. The objectives of this research are: 1) determining factors that influence agricultural land conversion, and 2) determining impact of agricultural land conversion toward farmer’s welfare. The research was conducted at Lembang and Parongpong Sub District, Bandung Regency from June to August 2004. Primary data was collected through a survey on 61 farmers and secondary data from related institutions were utilized. The data was analyzed using : 1) descriptive analysis; 2) multiple linear regression; and 3) logistic binary regression. This study revealed that agricultural land conversion at Lembang and Parongpong Sub Districts within a decade, from 1992 to 2002 was 3.134,49 hectare (25%) or 313,5 hectare per year (2,96 %). Forest land use was greatly decreased (-3.732,12 hectare or -68 %), bushes land use was highly increased (2.780,23 hectare or 13.26 %). Influential factors for the conversion were: (a) the density of population in 1992, (b) the density of agricultural land owners in 1992, (c) the density of agricultural land non-owners in 1992, the density increase of agricultural land non-owners, (d) the percentage of ‘idle’ land acreage and its increasing rate, (e) the number of poor people, (f) the village-sub district town distance. In general, agricultural land conversion would increase the probability of farmer’s welfare degradation. IndonesianKonversi lahan pertanian terjadi sebagai konsekwensi logis dari perkembangan wilayah. Konversi lahan pertanian seringkali menimbulkan dampak negatif terutama dalam konteks ketahanan pangan dan kondisi sosial ekonomi petani. Studi dalam aspek makro terhadap konversi lahan pertanian telah banyak dilakukan, tetapi studi dalam aspek mikro masih relatif terbatas. Tujuan penelitian ini adalah 1) mencari faktor-faktor yang mempengaruhi konversi lahan pertanian dan 2) menerangkan pengaruh konversi lahan pertanian terhadap perubahan kesejahteraan petani. Penelitian dilakukan di Kecamatan Lembang dan Kecamatan Parongpong, Kabupaten Bandung, dari bulan Juni-Agustus 2004. Data primer diperoleh melalui survei wawancara terhadap 61 petani responden, sedangkan data sekunder diperoleh dari instansi terkait. Analisis data menggunakan 1) analisis deskriptif, 2) analisis regresi linier berganda, dan 3) analisis regresi logistik binari. Hasil penelitian menunjukan bahwa di Kecamatan Lembang dan Parongpong dalam periode 10 tahun (1992-2002) telah terjadi konversi lahan pertanian seluas 3.134,49 hektar (25%) atau 313,5 hektar per tahun (2,96%). Penggunaan lahan hutan merupakan yang paling banyak berkurang (-3.732,12 hektar atau -68%), lahan semak mengalami peningkatan paling tinggi ((2.780,23 hektar atau 1.326%). Beberapa faktor yang mempengaruhi konversi lahan pertanian adalah kepadatan penduduk tahun 1992, kepadatan petani pemilik lahan pertanian tahun 1992, kepadatan petani nonpemilik lahan pertanian tahun 1992, peningkatan kepadatan petani nonpemilik lahan pertanian, persentase luas lahan guntai dalam desa, peningkatan jumlah penduduk miskin, dan jarak desa ke kota kecamatan. Secara umum, konversi lahan pertanian berpeluang menurunkan kesejahteraan petani.